Transformation of business under the influence of artificial intelligence - Buha Vesna; Lečić Rada; Berezljev Ljiljana (Trendovi u Poslovanju)
The use of artificial intelligence (AI) in business ventures is becoming more common. Innovative ideas and concepts, along with AI, lead to greater efficiency in work. How far-reaching are its possibilities, and where should the limits be set? Examples of good business practices such as AI in customer service provide answers to these and other research questions. The Dutch airline company KLM Royal Dutch Airlines has introduced "AI - assisted human agent". By introducing artificial intelligence, KLM achieves a 35% increase in work efficiency. Monitoring the outcome of the use of AI, user reactions and business effects, clearly indicates the possibilities and adequate limits in which it is possible to leave decision-making to machines, and which segment of work remains the responsibility of human resources. Research results of Forbes Advisor (2023) indicate that the most common use of AI is in Customer Service, Cyber Security, Digital Personal Assistants, Customer Relationship Management (CRM), etc. The effects of using AI are expected to increase productivity, improve customer relations, increase sales, etc.